Longitudinal Alterations in Prefrontal Resting Brain Connectivity in Non-Treatment-Seeking Young Adults With Cannabis Use Disorder - Camchong, Jazmin; Collins, Paul F.; Becker, Mary P.; Lim, Kelvin O.; Luciana, Monica (Frontiers in Psychiatry, 2019)
BACKGROUND: Cannabis is increasingly perceived as a harmless drug by recreational users, yet chronic use may impact brain changes into adulthood. Repeated cannabis exposure has been associated with enduring synaptic changes in executive control and reward networks. It is important to determine whether there are brain functional alterations within these networks in individuals that do not seek treatment for chronic cannabis abuse. METHODS: This longitudinal study compared resting state functional connectivity changes in executive control and reward networks between 23 non-treatment seeking young adults with cannabis use disorder (6 females; baseline age M = 19.3 ±1.18) and 21 age-matched controls (10 females; baseline age M = 19.4 ±0.65) to determine group differences in the temporal trajectories of resting state functional connectivity across a two-year span. RESULTS: Results showed (i) significant increases in resting state functional connectivity between caudal anterior cingulate cortex and precentral and parietal regions over time in the control group, but not in the cannabis use disorder group and (ii) sustained lower resting state functional connectivity of anterior cingulate cortex seeds with frontal and thalamic regions in the cannabis use disorder group vs the age-matched controls. Resting state functional connectivity strength was correlated with cannabis use patterns in the cannabis use disorder sample. CONCLUSION: Longitudinal alterations in intrinsic functional organization of executive control networks found in non-treatment seeking young adults with cannabis use disorder (when compared to age-matched controls) may impact regulatory control over substance use behavior. Current findings were limited to examining executive control and reward networks seeded in ACC and NAcc respectively, future studies with larger sample sizes and enough power are needed to conduct exploratory analyses examining rsFC of other networks beyond those within the scope of the current study.